The involvement of the GPR39-Zn(2+)-sensing receptor in the pathophysiology of depression. Studies in rodent models and suicide victims - Młyniec, Katarzyna; Doboszewska, Urszula; Szewczyk, Bernadeta; Sowa-Kućma, Magdalena; Misztak, Paulina; Piekoszewski, Wojciech; Trela, Franciszek; Ostachowicz, Beata; Nowak, Gabriel (Neuropharmacology, 2014)
Zinc is one of the most important trace elements in our body. Patients suffering from depression show lower serum zinc levels compared to healthy controls. Zincs antagonism to the glutamatergic system seems to be responsible for mood recovery. Recent years have shown that zinc may regulate neurotransmission via the metabotropic GPR39 receptor. Activation of the GPR39-Zn(2+)-sensing receptor (GPR39) triggers diverse neuronal pathways leading to a cAMP-responsive element binding the protein (CREB) expression, which then induces synthesis of the brain-derived neurotrophic factor and, in turn, activation of the Tropomyosin receptor kinase B (TrkB) receptor. In the present study, we investigated the alteration of the GPR39 in different models of depression, such as zinc deficiency and olfactory bulbectomy and in suicide victims. Additionaly, we focused on CREB-BDNF/TrkB under zinc deficient conditions in mice. To demonstrate depressive-like behaviour, a standard and modified forced swim test (FST) was performed. To evaluate expression of GPR39, CREB, BDNF and TrkB, Western Blot analysis was used. Zinc deficient mice and rats showed decreased GPR39 expression in the hippocampus and frontal cortex. A decreased level of hippocampal and cortical GPR39 was also observed in suicide victims. In contrast, increased GPR39 in the hippocampus of olfactory bulbectomized rats was observed. Additionally, we found a decreased expression of CREB, BDNF and TrkB only in the hippocampus of zinc-deficient mice. Our present study demonstrates the associacion of the GPR39 Zn(2+)-sensing receptor in the pathomechanism of depression. Down-regulation of CREB, BDNF, TrkB and GPR39 receptor found under zinc-deficient conditions in the hippocampus, may play an important role in the pathophysiology of mood disorders, since most of patients suffering from depression show lower serum zinc. •Zinc deficiency causes depression-like behaviour in the modified forced swim test.•Zinc deficiency in rodents as well as suicide victims decrease the expression of the GPR39 receptor.•Zinc deficiency induces a reduction in CREB-BDNF/TrkB in the hippocampus, but not in the frontal cortex.•GPR39-down regulation may be involved in the pathophysiology of depression.